Using Restorative Practices to Prepare Teachers to Meet the Needs of Young Adolescents - Jamie Silverman; Molly Mee (MDPI AG, 2018)
Recent news on school safety and efforts to improve school climate underscores the importance of building positive student relationships and resolving conflict in our nation’s classrooms. Restorative practices are currently gaining credibility and popularity as a means to build classroom and peer relationships. Through a descriptive study, we explored how to model the restorative practice of community circles with teacher candidates to prepare them to use the approach with their future middle school students. We describe how a teacher educator engaged middle-level teacher candidates with community circles in an internship seminar for this purpose. This article illustrates the powerful effects restorative practices had on the teacher candidates’ peer relationships and the connections they made about teaching young adolescent students. We also provide a step-by-step guide for implementing this practice in middle level teacher education programs.